Workplace sexual harassment and depressive symptoms: a cross-sectional multilevel analysis comparing harassment from clients or customers to harassment from other employees amongst 7603 Danish employees from 1041 organizations - Maria K. Friborg; Jørgen V. Hansen; Per T. Aldrich; Anna P. Folker; Susie Kjær; Maj Britt D. Nielsen; Reiner Rugulies; Ida E. H. Madsen (BMC, 2017)
Abstract Background Previous research has reported that sexual harassment can lead to reduced mental health. Few studies have focused on sexual harassment conducted by clients or customers, which might occur in person-related occupations such as eldercare work, social work or customer service work. This study examined the cross-sectional association between sexual harassment by clients or customers and depressive symptoms. We also examined if this association was different compared to sexual harassment conducted by a colleague, supervisor or subordinate. Further, we investigated if psychosocial workplace initiatives modified the association between sexual harassment by clients or customers and level of depressive symptoms. Methods We used data from the Work Environment and Health in Denmark cohort study (WEHD) and the Work Environment Activities in Danish Workplaces Study (WEADW) collected in 2012. WEHD is based on a random sample of employed individuals aged 18-64. In WEADW, organizational supervisors or employee representatives provided information on workplace characteristics. By combining WEHD and WEADW we included self-reported information on working conditions and health from 7603 employees and supervisors in 1041 organizations within 5 occupations. Data were analyzed using multilevel regression and analyses adjusted for gender, age, occupation and socioeconomic position. Results Exposure to workplace sexual harassment from clients or customers was statistically significantly associated with a higher level of depressive symptoms (2.05; 95% CI: 0.98-3.12) compared to no exposure. Employees harassed by colleagues, supervisors or subordinates had a higher mean level of depressive symptoms (2.45; 95% CI: 0.57-4.34) than employees harassed by clients or customers. We observed no statistically significant interactions between harassment from clients and customers and any of the examined psychosocial workplace initiatives (all p > 0.05). Conclusions The association between sexual harassment and depressive symptoms differed for employees harassed by clients or customers and those harassed by colleagues, supervisors or subordinates. The results underline the importance of investigating sexual harassment from clients or customers and sexual harassment by colleagues, supervisors or subordinates as distinct types of harassment. We found no modification of the association between sexual harassment by clients or customers and depressive symptoms by any of the examined psychosocial workplace initiatives.